A GIS-based study on the spatial distribution and revitalization patterns of industrial heritage in northeast China - Fu, Yinghang; Lee, Sang-Jun; Kim, Mi-Sun; Wang, Xinying; Dong, Weidan (Frontiers in Environmental Science, 2026)
IntroductionIndustrial heritage revitalization is a key driver of urban renewal and industrial transformation in old industrial bases. However, there is a lack of systematic quantitative evidence at the regional scale regarding the spatial clustering of industrial heritage and the differentiated revitalization patterns across different urban typologies in Northeast China.MethodsThis study integrates national and provincial industrial heritage lists for Northeast China. It constructs five revitalization patterns—cultural exhibition, commercial development, landscape -park reuse, in-production activation, and static conservation—and applies GIS-based spatial statistical methods to analyze the spatial clustering characteristics and revitalization differentiation.ResultsThe study reveals a “local clustering and overall dispersion” pattern, with high-density clusters around major urban agglomerations and industrial corridors. The urban typologies follow a policy-based classification into core cities, nodal cities, and resource-based cities. A clear “space–function coupling” differentiation is observed: core cities have the most diverse revitalization patterns, mainly dominated by cultural exhibition and commercial development; nodal cities show corridor-like distributions along transportation and industrial corridors, with in-production activation and exhibition functions interwoven; resource-based cities are primarily dominated by static conservation and landscape–park reuse.DiscussionFurther analysis suggests that population size and economic strength (GRP) influence revitalization choices and functional diversity. Based on the findings, the study proposes a “core–radiation–infill” regional activation pathway, offering quantitative evidence and differentiated policy implications for industrial heritage conservation, urban renewal, and industrial transformation in Northeast China.